Reforming the Regulatory Impact Assessment to Restore Regulatory Rationality in Indonesia’s Fast-Track Legislation - Alfin Dwi Novemyanto; Rismawati Nur; Muhammad Rosyid Ridlo (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study aims to analyze the failure of implementing the Regulatory Impact Assessment (RIA) in maintaining regulatory rationality within Indonesia’s fast-track legislation practices and to formulate a reform model grounded in Max Weber’s theory of rational-legal authority and the principles of good regulatory governance. Methodology: This research employs a normative juridical method using conceptual and statutory approaches. Legal materials were collected through library research and analyzed qualitatively using rational-legal reasoning to evaluate the effectiveness of the RIA mechanism in ensuring the quality of lawmaking processes. Findings: The study finds that RIA has not been substantively implemented in Indonesia’s fast-track legislative process, resulting in a shift from legal rationality to pragmatic political rationality. This condition has weakened legal legitimacy, caused policy overlaps, and eroded public trust in legislative institutions. The lack of public participation, transparency, and evidence-based analysis is identified as the main factor behind the ineffective implementation of RIA. Practical implications: The findings highlight the urgency of adaptive RIA reform through strengthened inter-agency coordination, the adoption of an open regulatory data system, and the establishment of an independent regulatory evaluation body. This model can serve as a practical framework for policymakers to ensure rational, transparent, and accountable legislative processes. Originality/value: This study offers an original contribution by integrating Weberian legal rationality theory into the reform design of RIA in Indonesia. It presents a novel conceptual framework for reinforcing legal legitimacy and regulatory quality through the institutionalization of RIA as a mechanism of rational-legal authority in a modern Rechtsstaat.